Assessing safety culture of professional pilots within selected South African based aviation organisations - Davids, Amirah Fatoma Gadija (University of the Western Cape, 2016)
Magister Commercii - MCom === The aviation industry is one of many industries which is known to be a high-risk industry. Although it is a high risk industry, little research has been conducted within the industry especially with regards to safety culture. Safety culture is pivotal within the aviation industry as it reduces the potential to large scale disasters. While airlines are deemed to be highly reliable, when an accident occurs the cause usually tends to be human error. The aim of this study was to assess safety culture of professional pilots within selected South African based aviation organisations. This study utilized a safety culture quantitative survey instrument in order to collect data from pilots at selected South African based aviation organisations. The survey consisted of five themes (organisational commitment, management involvement, accountability systems, reporting systems and pilot empowerment). The pilots were required to respond to 49-item statements on a 5 point-likert scale, by only choosing one answer per statement. The results indicated that a majority of the participants had responded positively towards the items which represented a healthy safety culture within the selected South African based aviation organisations. Furthermore, a highly positive correlation exists between the themes of organisational commitment and management involvement. Multiple regression analysis showed there is an association between the five themes of safety culture with organisational commitment being a dependent variable. No significant difference was found between biographical information (such as rank, years of experience and flying hours), along with either the themes of organisational commitment or pilot empowerment.